Metabolic Profiling Analysis of Liver in Landes Geese During the Formation of Fatty Liver via GC-TOF/MS - Yu, Yuzhu; Lyu, Wentao; Fu, Zixian; Fan, Qian; Xiao, Yingping; Ren, Ying; Yang, Hua (Frontiers in Physiology, 2022)
Fatty liver production results from the process of overfeeding geese, inducing a dramatic increase in de novo liver lipogenesis. To investigate the alteration of liver metabolites by overfeeding, especially lipid metabolites, and the potential pathways causing these changes, 60 Landes geese at 65 days old were raised in 3 groups with 20 geese per group, namely, the D0 group (free from gavage), D7 group (overfeeding for 7 days), and D25 group (overfeeding for 25 days). At 90 days old, segments of liver tissue were collected from 10 geese of each group for gas chromatography time-of-flight/mass spectrometry (GC-TOF/MS) analysis. A large number of endogenous molecules in the livers of geese were altered dramatically by overfeeding. In the livers of overfed geese, the level of oleic acid was observed to continuously increase, while the levels of phenylalanine 1, methyl phosphate, sulfuric acid, and 3-hydroxybenzaldehyde were decreased. The most significantly different metabolites were enriched in amino acid, lipid, and nucleotide metabolism pathways. The present study further supports the idea that Landes geese efficiently produce fatty liver, and potential biomarkers and disturbed metabolic pathways during the process of forming fatty liver were identified. In conclusion, this study might provide some insights into the underlying mechanisms of fatty liver formation.